VD_FINDINFO HC / 2013 / 411 vom 25. Juni 2013 - VD Tribunal cantonal (2013)
AVANCE DE FRAIS, LOI SUR LA FUSION | 29 al. 2 Cst., 105 LFus, 106 LFus, 106 al. 1 CPC (CH), 107 al. 1 let. f CPC (CH), 98 CPC (CH)